Entrepreneurial self-confidence, perceived desirability and feasibility of hospitality business and entrepreneurial intentions of hospitality management technology students. Issue 2 (July 2021) - Otache, Innocent; Edopkolor, James Edomonyi; Okolie, Ugochukwu Chinonso
Abstract: Drawing on insights from the entrepreneurial event model, this study aims to examine the mediating effect of entrepreneurial self-confidence (ESC) on the relationship between perceived entrepreneurial desirability (PED), perceived entrepreneurial feasibility (PEF) and entrepreneurial intentions (EIs) among hospitality management technology (HMT) students. A descriptive correlational research design was adopted and data were collected from a randomly selected sample of 157 final year HMT students using a self-reported questionnaire. PLS-SEM was employed to test the hypotheses. The results showed that PED and PEF were positively associated with HMT students' ESC and EIs. Further analysis indicated that ESC significantly predicted HMT students' EIs and mediated the links between PED and EIs and between PEF and EIs of HMT students. These findings suggest that positive and strong perceptions of desirability and feasibility of a hospitality business activate high levels of ESC among HMT students and, high ESC, in turn, enhances their EIs. The findings have practical implications for higher education institutions that offer HMT course and governments. This study does not only validate the entrepreneurial event model in different contexts but also modifies the model by empirically demonstrating the indirect effects of PED and PEF on EIs through ESC. Highlights: Drawing on insights from the entrepreneurial event model, this study examines the mediating effect of ESC on the relationship between PED, PEF and EIs among HMT students. PED and PEF were positively associated with HMT students' ESC and EIs. ESC significantly predicted HMT students' EIs and mediated the links between PED and EIs and between PEF and HMT students' EIs respectively.